After the death of nature : Carolyn Merchant and the future of human-nature relations - Worthy, Kenneth, 1961-; Allison, Elizabeth; Bauman, Whitney (New York, NY : Routledge, 2019)
Carolyn Merchant's foundational 1980 book The Death of Nature: Women, Ecology, and the Scientific Revolution established her as a pioneering researcher of human-nature relations. Her subsequent groundbreaking writing in a dozen books and over one hundred peer-reviewed articles have only fortified her position as one of the most influential scholars of the environment. This book examines and builds upon her decades-long legacy of innovative environmental thought and her critical responses to modern mechanistic and patriarchal conceptions of nature and women as well as her systematic taxonomies of environmental thought and action. Seventeen scholars and activists assess, praise, criticize, and extend Merchant's work to arrive at a better and more complete understanding of the human place in nature today and the potential for healthier and more just relations with nature and among people in the future. Their contributions offer personal observations of Merchant's influence on the teaching, research, and careers of other environmentalists.
After the death of nature: introduction -- Part I: Environmental philosophy and ethics and ecofeminism: Before the death of nature: Carolyn Iltis, the Carolyn Merchant few people know -- The death of nature or divorce from nature? -- Carolyn Merchant's the death of nature: launching new trajectories in interdisciplinary research -- From a partnership to a fidelity ethic: framing an old story for a new time -- Bewitching nature -- Leading and misleading metaphors: from organism to anthropocene -- Part II: Environmental history: Personal, political, and professional: the impact of Carolyn Merchant's life and leadership -- Carolyn Merchant and the ecological Indian -- All our relations: reflections on women, nature, and science -- The other scientific revolution: Calvinist scientists and the origins of ecology -- Carolyn Merchant and the environmental humanities in Scandinavia -- Part III: The politics of landscapes, embodiment, and epistemologies: Landscape, science, and social reproduction: the long-reaching influence of Carolyn Merchant's insight -- The spiritual politics of the Kendeng Mountains versus the global cement industry1 -- Toward a political ecology of environmental discourse -- Environmental history and the materialization of bodies -- A mighty tree is Carolyn Merchant -- Afterward -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Merchant, Carolyn; Human ecology; Nature -- Effect of human beings on; NATURE / Ecology; NATURE / Environmental Conservation & Protection; SOCIAL SCIENCE / Sociology / General